Identifikasi Faktor dan Model Tahapan Pengembangan Infrastruktur Pariwisata Terintegrasi di Provinsi Bengkulu - Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The tourism sector is one of the key drivers in boosting economic growth and community welfare. Although its contribution to Indonesia's Gross Domestic Product (GDP) is still relatively small, the potential of national tourism continues to show positive development, mainly supported by advances in technology, transportation, and telecommunications that facilitate mobility and access to tourism information. Globally, Indonesia's tourism competitiveness has increased significantly, as reflected in the rise in the Travel and Tourism Competitiveness Index by the World Economic Forum, particularly in terms of transportation infrastructure and tourism services. However, this improvement has not been evenly distributed across all regions. Foreign tourists are still focused on certain destinations such as Bali, Riau Islands, and DKI Jakarta, while several other provinces have not been able to attract tourists optimally. The province of Bengkulu, for example, shows a fluctuating trend with a downward trend in the number of foreign tourist visits and is recorded as one of the regions with the lowest number of visits in Indonesia. This condition indicates an imbalance in tourism development between regions and the need for more effective and integrated strategies to encourage increased regional tourism attractiveness and competitiveness.